Screening Analysis Stabilitas Lereng Bendungan Urugan Akibat Gempa Di Indonesia - Mahdi Ibrahim Tanjung; Reza Nirwana Sari; Ranisa Ghafara (JURNAL TEKNIK HIDRAULIK, 2017)
The 2010 seismic hazard map shows the acceleration of the maximum design earthquake (MDE) scenario has increased approximately 2 fold, this case raises the question of how the dam designed by the pervious seismic load. Today Indonesia has more than 210 large dams. Therefore it is necessary to do screening analysis to find out which dam needs to be more detailed analysis and which are not. Screening analysis is done for embankment dam with fondation not on soft soil, or on the body or foundation of the dam there is a material that can lose shear strentgh due to dynamic load. Screening analysis begins with determining a typical dam for use in parametric studies of embankment parameters, variation of slope, and seismic loads on the safety of slope stability due to earthquake. The parametric study were then used as a basis for screening of embankment dam seismic slope stability. From 38 rockfill dam analyzed, all of them passed the screening under MDE scenario, and from 55 earthfill dam 40% of them not pass the screening on the 50% remaining free board requirement due to MDE scenario so that further analysis was needed. Previously to know the seismic slope stabilit of embankment dam doe to seismic hazard map revision, usually done one by one analysis with pseudostatic method, in this paperfor the first time in Indonesia applied screening analysis for slope stability analysis of dam due to earthquake.